Investigating online recognition for blood donor retention: an experiential donor value approach. Issue 2 (7th April 2014) - Chell, Kathleen; Mortimer, Gary; Boenigk, Silke
<x xml:space="preserve">Abstract</x> Recognising that charitable behaviour can be motivated by public recognition and emotional satisfaction, not‐for‐profit organisations have developed strategies that leverage self‐interest over altruism by facilitating individuals to donate conspicuously. Initially developed as novel marketing programmes to increase donation income, such conspicuous tokens of recognition are being recognised as important value propositions to nurture donor relationships. Despite this, there is little empirical evidence that identifies when donations can be increased through conspicuous recognition. Furthermore, social media's growing popularity for self‐expression, as well as the increasing use of technology in donor relationship management strategies, makes an examination of virtual conspicuous tokens of recognition in relation to what value donors seek particularly insightful. Therefore, this research examined the impact of experiential donor value and virtual conspicuous tokens of recognition on blood donor intentions. Using online survey data from 186 Australian blood donors, results show that in fact emotional value is a stronger predictor of intentions to donate blood than altruistic value, whereas social value is the strongest predictor of intentions if provided with recognition. Clear linkages between dimensions of donor value (altruistic, emotional and social) and conspicuous donation behaviour (CDB) were identified. The findings provide valuable insights into the use of conspicuous donation tokens of recognition on social media and contribute to our understanding into the under‐researched areas of donor value and CDB. Copyright © 2014 John Wiley & Sons, Ltd.